IMPROVEMENT METHODS OF DIAGNOSIS THE VISUAL ANALYSER OF PATIENTS WITH MULTIPLE SCLEROSIS - A. V. Kovalenko (Bûlleten' Sibirskoj Mediciny, 2013)
137 (274 eyes) relapsing-remitting multiple sclerosis patients have been given detailed neuroophthalmologic examination. 58 of these patients (74 eyes) had a previous history of optic neuritis. As a result, the most informative methods of examination have been identified. These include the estimation of the frequency characteristics of the vision (vizokontrastoperimetriya, low-contrast tests Sloan), standard static automated perimetry, pattern visual evoked potentials, and optical coherence tomography which is used to measure macular volumes and retinal nerve fiber layer thickness. The above – mentioned methods make it possible to reveal the involvement of the optic analyzer in the inflammatory and neurodegenerative process at the pre-clinical stage. The obtained results allow us to recommend inclusion of the methods in the standard algorithm for the examination of patients with probable multiple sclerosis.